Hot metal : material culture and tangible labour - Stein, Jesse Adams (Studies in design and material culture., 2017)
This work focuses on the experience of Australian print-workers between the 1960s and 1980s, concentrating on labour, production, design, and culture in the context of deindustrialisation.